Prospective teachers' perceptions of web specific self-efficacy - Gömleksiz, Mehmet Nuri; Erten, Pinar (Ankara University, 2013)
The main aim of this study is to explore prospective teachers' perceptions of web specific self-efficacy. Data for the study were collected through a 21-item, five-point Likert-style scale from a total of 807 prospective teachers at the Science Faculty, Faculty of Humanities and Social Sciences, Faculty of Education and College of Physical Education and Sports at Fi{dotless}rat University. Web specific self-efficacy scale was administered to all participants. Independent samples t-test, one way ANOVA and Kruskal Wallis H were utilized to analyze the data. Findings revealed that male prospective teachers had higher web specific self-efficacy level than female students. Prospective teachers enrolled at the department of Computer and Instructional Technologies had higher self-efficacy level than those enrolled at other departments. Web specific self-efficacy level of the graduates of numerical field was higher than other field graduates. Those who accessed the internet at home had higher levels of self-efficacy than those who had access at other places. Moreover, the prospective teachers having more on-line hours per week, in general, displayed more positive web specific self-efficacy than those who had less access. Some useful implications are discussed based on the research findings.
Ö?retmen adaylarının webe özgü özyeterlik algıları
Keywords: Internet; Prospective teacher; Self-efficacy; Web; Web specific self-efficacy